2018
DOI: 10.1038/s41598-018-24508-7
|View full text |Cite
|
Sign up to set email alerts
|

Tracing of the fecal microbiota of commercial pigs at five growth stages from birth to shipment

Abstract: The intestinal microbiota affect various physiological traits of host animals such as brain development, obesity, age, and the immune system. In the swine industry, understanding the relationship between intestinal microbiota and growth stage is essential because growth stage is directly related to the feeding system of pigs, thus we studied the intestinal microbiota of 32 healthy pigs across five sows at 10, 21, 63, 93, and 147 d of ages. The intestinal microbiota were altered with growth of pigs and were sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
88
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(109 citation statements)
references
References 40 publications
18
88
3
Order By: Relevance
“…At a family level, the main changes in abundance appeared between post-weaning and finishing in accordance with previous findings [21]. Furthermore, we demonstrated that the microbiota composition kept evolving during all tested stages based on the NMDS and the relative abundance at family and genus levels in line with the results of Kim et al [24] despite previous studies demonstrating that a stabilized composition of the microbiota was reached around three months of age [22,23].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…At a family level, the main changes in abundance appeared between post-weaning and finishing in accordance with previous findings [21]. Furthermore, we demonstrated that the microbiota composition kept evolving during all tested stages based on the NMDS and the relative abundance at family and genus levels in line with the results of Kim et al [24] despite previous studies demonstrating that a stabilized composition of the microbiota was reached around three months of age [22,23].…”
Section: Discussionsupporting
confidence: 92%
“…In our experiment, the diversity increased when the pigs were aging, as previously observed [20][21][22]. At the phylum level, the Firmicutes' relative abundance increased especially between post-weaning and finishing periods [22] and remained stable during the late-stages [23]. In accordance with Han et al [23], the relative abundance of Spirochaetes increased during the finishing period.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The second potential activity of the Peptiva product investigated in this study was the ability to change or modulate the composition of the gut microbiome in weaned pigs. Since the composition of gut microbial communities has been associated with the health status and performance of individual hosts [3,[35][36][37], compounds that can change gut symbiont profiles have the potential to be developed as tools to improve critical livestock production parameters [38]. To this end, fecal bacterial communities were used as a proxy for gut microbiome composition analysis in weaned pigs, from which two main observations were made: evidence of bacterial succession between Phase II and Phase III in control-fed animals, and a stage-specific effect in Pep-fed pigs.…”
Section: Discussionmentioning
confidence: 99%